Alternative splicing patterns of doublesex reveal a missing link between Nix and doublesex in the sex determination cascade of Aedes albopictus. (2nd December 2020) - Jin, Binbin; Zhao, Yijie; Dong, Yunqiao; Liu, Peiwen; Sun, Yan; Li, Xiaocong; Zhang, Xin; Chen, Xiao‐Guang; Gu, Jinbao
Abstract: Sexual development in insects is regulated by a complicated hierarchical cascade of sex determination. The primary signals are diverse, whereas the central nexus doublesex ( dsx ) gene is relatively conserved within the pathway. Aedes ( Stegomyia ) albopictus is an important vector with an extensive worldwide distribution. We previously reported that Ae. albopictus dsx ( Aalbdsx ) yields one male‐ ( Aalbdsx M ) and three female‐specific isoforms ( Aalbdsx F1‐3 ); however, the spatiotemporal expression profiles and mechanisms regulating sex‐specific alternative splicing require further investigation. In this study, we demonstrated that the Aalbdsx M messenger RNA (mRNA) represents the default pattern when analyzed in human foreskin fibroblasts and HeLa cells. We combined reverse transcription polymerase chain reaction with RNA immunoprecipitation using specific antibodies against tagged Ae. albopictus male‐determining factor AalNix and confirmed that AalNix indirectly regulates dsx pre‐mRNA and regulates its alternative splicing. During the early embryo stage (0–2 and 4–8 h), maternal dsx F and default splicing dsx M were detected in both sexes; the expression of dsx M then decreased until sufficient AalNix transcripts accumulated in male embryos at 20–24 h. These findings suggest that one or more potential dsx splicing enhancers can shift dsx M to dsx F in both sexes; however, the presence of Nix influences the function of this unknown splicing enhancer and ultimately leads to the formation of dsx M in males. Finally, our results provide important insight into the regulatory mechanism of dsx alternative splicing in the mosquito. Abstract : We demonstrated that the Aalbdsx M mRNA represents the default pattern when analyzed in HFF‐1 and HeLa cells. We combined RT‐PCR with RNA immunoprecipitation using specific antibodies against tagged Aedes albopictus male‐determining factor AalNix and confirmed that AalNix indirectly binds dsx pre‐mRNA and regulates its alternative splicing. During the early embryo stage (0–2 and 4–8 h), maternal dsx F and default splicing dsx M were detected in both sexes and then dsx M decreased until the AalNix transcripts accumulated enough in the 20–24 h male embryos. These findings suggest that one or more potential dsx splicing enhancers can shift dsx M to dsx F in both sexes; however, the appearance of Nix influences the function of this unknown splicing enhancer and ultimately led to the formation of dsx M in males.